EXPLORING SKILLS NEEDED FOR DISRUPTIVE DIGITAL BUSINESS - Handayani, Dewi Wahyu; Tjakraatmadja, Jann Hidajat; Ghazali, Achmad (The International Journal of Accounting and Business Society, 2020)
Research Purpose – In today’s disruptive digital business era, many new business models, such as digital start-ups, have emerged, and this phenomenon needs workers with particular skills. The aims of this preliminary empirical research paper are to explore and identify the skills needed for disruptive digital business in the Indonesian context, particularly in the Jakarta region.Design/methodology/approach – This qualitative study conducted semi-structured interviews with ten respondents from various types of Indonesian start-ups, such as unicorn start-up, financial technology and education technology, that have been in operation four to 12 years. The interviews were based on five core questions with the purpose of exploring respondents’ experience regarding skills needed and challenges faced at work in disruptive digital business. Observation was conducted at the Education Technology start-up office located in Jakarta with an aim to investigate workplace environment, and triangulation was used to validate the interviews’ results.Findings – The results show that (1) innovativeness, (2) leadership skills, (3) social interaction, (4) initiative mindsets, (5) self-disruption, (6) critical thinking, (7) management, and (8) analytical thinking are eight pivotal skills identified for managing disruptive digital business.Practical implications – Innovativeness, leadership and social interaction are the top three skills that are essential for actors in Indonesian digital start-ups to have competitive advantages in this disruptive digital business era.Original/value – This paper explores skills needed for the disruptive digital era in an Indonesian context.Keywords – skills concepts, disruptive, digital businessPaper type – Research paper